(untitled) (Kairaranga, 2008)
In this article I outline different elements of action research in an attempt to describe and define participatory action research (PAR). There is a lot more material available to readers these days, some of which I will refer you to in this article. I see my role here is to summarise enough of this material to help support your reading of the other articles that appear in this issue of Kairaranga. This material (I have tried to use work from Aotearoa New Zealand in the first instance) refers to the ethical, political and context characteristics of PAR, as well as the design and format for conducting such research.